Antonenko, Oksana y Pinnick, Kathryn (eds.) (2005): Russia and the European Union. Johnson, Debra y Robinson, Paul (eds.) (2005): Perspectives on EU-Russia Relations - Morales, Javier (UNISCI Discussion Papers, 2005)
Sin resumen